Peculiarities of forming of linkages and their impact on structural policies in the agroindustrial production - Томілін, О. О. (Scientific Progress & Innovations, 2017)
The article carried out a systematic analysis of the current state of interbranch economic relations in the agroindustrial production; it shows the specific formation and development of interbranch economic relations in the agricultural economy and its impact on structural policies of agroindustrial production; it substantiated the main factors of the formation of interbranch system of economic relations in agroindustrial production. Structural policy is considered as multifaceted concept, which reflects the ratio of different interrelated and interdependent elements of economic systems. The author drew a conclusion about the basic mechanisms of structural adjustment policies, the implementation of integrated programs, free pricing, competition, accumulation and flow of capital from one branch to another. It is determined that the main objectives of structural and organizational tools of regulation are customs tariff, social and psychological, market pricing, finance and credit, innovation and investment. The main problems of economic development of Ukraine which cause activation of restructuring the national economy are structural deformation in the fields of agroindustrial production, ineffective level of modern production technologies, inefficiency interbranch relations of agricultural industries, weak economic management mechanism for all sectors of agroindustrial production.